Biocontrol of Rhizome Rot of Ginger(Zinfiber officinale) by Antagonistic Microorganisms - Shanmugham V (Department of plant Pathology, College of Horticulture, 1996)
Rhizome rot is one of the most destructive diseases of ginger in Kerala. The pathogen was isolated from infected rhizomes and its pathogenicity established. The pathogen was characterized and identifies as Pythium aphanidermatum (Edson) Fitz. based on its cultural and morphological characters. Soil microorganisms were isolated from the rhizosphere of healthy ginger plants among the rhizome rot affected plants in the diseased field and were quantitatively and qualitatively estimated. The population of bacteria was maximum followed by actinomycetes and fungi. A diversified group of soil microflora consisting of nine species of fungi belonging to four genera viz. Rhizopus, Aspergillus, Trichoderma and Eupenicillium, one actinomycete of Streptomyces sp. and four species of bacteria which were distinguished from each other based on their colony characters as B1, B2, B3 and B4. Antagonistic properties of the microorganisms isolated were studied against the pathogen P. aphanidermatum in dual culture. Rhizopus sp. and Aspergillus carneus showed the dual culture reaction of intermingling and overgrowth with the pathogen which is not considered as an antagonistic reaction. A. niger exhibited the reaction of inhibition at a distance and disintegration of pathogen while die-back and distintegration of the pathogen was shown by A. fumigatus, A. flavus and Trichoderma viride. Both these characters are considered strong antagonism. A. flavus (sclerotial), Eupenicillium javanicum ITCC No. 4.595 and E. javanicum ITCC No. 4.596 have the reaction of mutual inhibition on contact with the pathogen in dual culture which is not considered as promising antagonistic property. Inhibitory properties of antagonists using cell free culture filtrates were estimated and found that A. niger inhibited 100 per cent growth of the pathogen. While A. fumigatus, T. viride and A. flavus inhibited the growth of P. aphanidermatum by 42,20 and 60 per cent respectively. Among the different fungicides screend in in vitro, fytolan and Bordeaux mixture completely inhibited the growth of the pathogen. Indofil M-45 and emisan exhibited comparatively less inhibitory effect. While Bordeaux mixture showed complete inhibition of the growth of all the antagonists. Indofil M-45 exhibited less efficacy of inhibition against the antagonists. Result of the pot culture studies, indicated that, treatments A. niger – seed inoculation, A. flavus – seed inoculation and A. niger – soil application after 60 and 120 DAP had minimum rhizome rot incidence. The studies on the effect of treatments on yield in pot culture experiment showed that copper oxychloride 0.3% as soil drenching and mancozeb 0.3% as soil drenching recorded maximum yield per plant. Thus, the present study revealed that seed inoculation of A. niger in combination with either copper oxychloride 0.3 % or mancozeb 0.3% was found to be most effective in checking the incidence and severity of rhizome rot of ginger and increasing the yield of rhizomes. Seed inoculation of A. flavus in combination with mancozeb 0.3% and soil application of A. niger after 60 and 120 DAP with either copper oxyxhloride 0.3% or mancozeb 0.3% were also found to be promising treatments.